(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article is about Scientificnfiction (SF) is a unique literary genre that blends scientific concepts, imaginative worlds, and futuristic technologies. Translating science fiction presents specific challenges due to its hybrid nature, combining technical terminology with creative language. This article explores the key translation methods and strategies used in science fiction, focusing on linguistic, cultural, and stylistic aspects. It also examines how translators balance accuracy and creativity while preserving the author’s intent and reader engagement. The study highlights that successful translation of SF requires not only linguistic competence but also interdisciplinary knowledge and cultural sensitivity.